Suanzaoren Formulae for Insomnia: Updated Clinical Evidence and Possible Mechanisms - Zhou, Qi-Hui; Zhou, Xiao-Li; Xu, Meng-Bei; Jin, Ting-Yu; Rong, Pei-Qing; Zheng, Guo-Qing; Lin, Yan (Frontiers in Pharmacology, 2018)
Insomnia disorder is a widespread and refractory disease. Semen Ziziphi Spinosae, Suanzaoren, a well-known Chinese herbal medicine, has been used for treating insomnia for thousands of years. Here, we aimed to assess the available evidence of Chinese herbal formulae that contains Suanzaoren (FSZR) for insomnia according to high-quality randomized controlled trials (RCTs) and reviewed their possible mechanisms based on animal-based studies. Electronic searches were performed in eight databases from inception to November 2016. The primary outcome measures were polysomnography index and Pittsburgh sleep quality index. The secondary outcome measures were clinical effective rate and adverse events. The methodological quality of RCTs was assessed by Cochrane’s collaboration tool, and only RCTs with positive for 4 out of 7 for the Cochrane risk of bias domains were included in analyses. Thirteen eligible studies with 1454 patients were identified. Meta-analysis of high-quality RCTs showed that FSZR monotherapy was superior to placebo (P<0.01); FSZR plus Diazepam was superior to Diazepam alone (P<0.05); there were mixed results comparing FSZR with Diazepam (P>0.05 or P<0.05). Furthermore, FSZR caused fewer side effects than that of Diazepam. Suanzaoren contains complex mixtures of phytochemicals including sanjoinine A, Jujuboside A, spinosin and other flavonoids, which has sedative and hypnotic functions primarily mediated by the GABAergic and serotonergic system. In conclusion, the findings of present study supported that FSZR could be an alternative treatment for insomnia in clinic. FSZR exerted sedative and hypnotic actions mainly through the GABAergic and serotonergic system.